Keputusan Pembelian Konsumen Fitness Center Di Masa Pandemi Covid 19 - Nurendah, Yulia; Christina, Rachel (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
With the increase in public awareness of sports, it encourages many business opportunities in the sports field. One of them is the fitness center business. This study aims to: 1) to determine the effect of service quality on purchasing decisions on Celebrity Fitness products, 2) to determine the effect of facilities on purchasing decisions on Celebrity Fitness products, 3) to determine the effect of brand trust on purchasing decisions on Celebrity Fitness products, 4) to determine the effect of service quality, facilities, brand trust on purchasing decisions on Celebrity Fitness products. This study took objects (respondents) in Botani Square, Bogor city. Data were analyzed by SPSS (Reliability Test, Validity Test, Classical Assumption Test, Normality Test, Multicolonierity Test, Heteroscedasticity Test, Multiple Regression Analysis, Correlation Analysis, Coefficient of Determination, Statistical Hypothesis Test, Persial Test (t test), Simultaneous Significance Test (Test F)). The results of the analysis are as follows: 1) service quality has a positive effect on purchasing decisions, 2) facilities have a positive effect on purchasing decisions, 3) brand trust has a positive effect on purchasing decisions, 4) service quality, facilities, brand trust have a positive and significant effect on purchasing decisions Keywords: Brand Trust, Facilities, Service Quality, Purchasing Decisions